The Overcoming Life - Moody, D. L.; Nang ChanYeema (Orlando, FL USA Bridge-Logos, 2007)
Writen in a simple and practical way to encourgage belivers in the daily struggle of Christian warfare.
Keywords: Adult Nonfiction